2016
DOI: 10.1155/2016/5650290
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Physical and Chemical Characteristics of Composted Tea Tree (Melaleuca alternifoliaL.) with Pine Bark Growing Media in Tobacco (Nicotiana tabucumL.) Seedling Production

Abstract: The search for suitable organic growing media substitutes for pine bark based media combinations has been prompted by concerns over high costs and lack of availability to smallholder farmers coupled with increasing demand for soilless media in Zimbabwe. A trial was conducted for 12 weeks to investigate the suitability of tea tree compost-based substrates for tobacco seedling production as a substitute of the traditional pine bark growing media. The use of composted tea tree growing media in float trays signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Indeed, N content increased according to the vermicompost volume added to the substrate mixture, with the highest content found in T4 (0.52% N) and the lowest in T1 (0.15% N) (Table 3). Furthermore, Masaka et al (2016) demonstrated that the CEC and N content of native pine bark growing media are lower than those found in composted tea tree media, which is consistent with our results.…”
Section: Treatmentsupporting
confidence: 92%
“…Indeed, N content increased according to the vermicompost volume added to the substrate mixture, with the highest content found in T4 (0.52% N) and the lowest in T1 (0.15% N) (Table 3). Furthermore, Masaka et al (2016) demonstrated that the CEC and N content of native pine bark growing media are lower than those found in composted tea tree media, which is consistent with our results.…”
Section: Treatmentsupporting
confidence: 92%
“…e authors also revealed that stem elongation of transplants has an effect on the initiation of flowering of tobacco plants, with shorter plants delaying flowering. e study also revealed that the root, shoot and total dry mass are not important parameters when selecting an ideal tobacco seedling for transplanting [25]. Stress in plant cells quickly affects stem elongation rather than biomass during early growth.…”
Section: Correlation and Regression Analyses Of Measuredmentioning
confidence: 93%
“…The standard technique involves suspending polystyrene trays on benches or simple wire and irrigating the substrates regularly, whereas the floating tray system involves floating polystyrene trays on water and the container-growing system, which is used in tobacco seedling production [9][10][11] and for aromatic plants and herbs production [12]. Other researchers have experimented with various growth media on a variety of plants [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%